First Report of Tachinobia Repanda Boucek, 1977 (Hymenoptera: Eulophidae) in Brazil - C. H, Marchiori, (International Journal of Entomology, 2021)
This work reports the first occurrence of parasitoid Tachinobia repanda Boucek, 1977 (Hymenoptera: Eulophidae) in Brazil. The pupae were obtained by the flotation method. They were individually placed in gelatin capsules until the emergence of flies or their parasitoids. In the study, eleven pupae of Oxysarcodexia sp. (Diptera: Sarcophagidae) was obtained from a single pupa 10 parasitoids of the species T. repanda  emerged. The percentage of parasitism was 9.1%.
Keywords: savana; dipteran; Hymenoptera Parasitic; host